1990
DOI: 10.3758/bf03203132
|View full text |Cite
|
Sign up to set email alerts
|

The NASA/LRC computerized test system

Abstract: A new testing package, including apparatus and tasks, is described for the study of behavior of a variety of species in a variety of experiments. The package is described with respect to the kinds of comparative psychological investigations for which it is well suited. The preliminary data generated within this new testing paradigm demonstrate that the NASA/LRC Computerized Test System provides a flexible yet powerful environment for the investigation of behavioral and psychological processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
97
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 7 publications
1
97
0
Order By: Relevance
“…The test program was written in Visual Basic for Windows. When feedback was available for responses (see below), correctly completed trials were automatically rewarded by the computer with single 94 mg Bio-Serv food pellets through use of an automated pellet dispenser (for details, see Richardson et al, 1990). Children completed the experimental program on a Toshiba laptop computer.…”
Section: Apparatusmentioning
confidence: 99%
“…The test program was written in Visual Basic for Windows. When feedback was available for responses (see below), correctly completed trials were automatically rewarded by the computer with single 94 mg Bio-Serv food pellets through use of an automated pellet dispenser (for details, see Richardson et al, 1990). Children completed the experimental program on a Toshiba laptop computer.…”
Section: Apparatusmentioning
confidence: 99%
“…At this juncture, we must direct our discussion to monkeys, for a new perspective on their competencies has been established through the development of the Language Research Center's Computerized Test System (LRC-CTS; Rumbaugh, Richardson, Washburn, SavageRumbaugh, & Hopkins, 1989;Richardson, Washburn, Hopkins, Savage-Rumbaugh, & Rumbaugh, 1990;Washburn, Hopkins, & Rumbaugh, 1989). This system has not only been a successful automation of the Wisconsin General Test Apparatus , but it also has afforded us and dozens of other laboratories around the world an economical system for research into questions limited only by the researcher's vision and imagination.…”
Section: Rhesus Monkeys In Comparative Perspectivementioning
confidence: 99%
“…Another successful means of overcoming S-R spatial discontiguity by rhesus monkeys has involved joystick-based computerized tests (Richardson, Washburn, Hopkins, Savage-Rumbaugh, & Rumbaugh, 1990;Rumbaugh , Richardson, Washburn, Savage-Rumbaugh, & Hopkins, 1989;. Rumbaugh et al (1989) reported that two rhesus monkeys mastered control of a joystick to respond to a variety of stimuli on a computer monitor despite the fact that the joystick was located up to 6 inches away from the video screen.…”
mentioning
confidence: 99%